Gilles de la Tourette Syndrome Co-existing with Attention Deficit Hyperactivity Disorder in a 9-Year Old Nigerian Boy - Afe TO; Ogunsemi OO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Tourette disorder is an uncommon neuropsychiatric disorder characterised by involuntary tics and behavioural disturbances. The disorder is most prevalent in childhood. Only a few cases of Gilles disorder had been reported in Nigeria. The disorder shares some characteristics and association with many neuropsychiatric disorders hence, the diagnosis can be easily missed. This is a report of a 9-year old school boy with Tourette disorder with co-existing Attention Deficit Hyperactive Disorder (ADHD). The diagnosis in this child was missed on initial assessment, hence this report highlights the need for high index of suspicion when children present with involuntary tics.